Application architecture to efficiently manage formal and informal m-learning. A case study to motivate computer engineering students (2015)
Recent research is focusing on methods that enable effective consumption of digital content. Students are continually exposed to streams of digital content. An information system for learning was designed. Such a tool intends to connect learning in formal channels with the ability to learn in informal channels. The proposed methodology built upon the application was tested through a quasi-experimental research, implementing and evaluating its influence on how engineering students learnt in an advanced engineering course where concepts are complex. The sample is of fifty-eight students enrolled in Computer Engineering at Universidad de Almería. Their knowledge was evaluated using a specifically designed exam. Results suggest that the effectiveness of the methodology used and the learning tool itself were both robust and fulfilled the hypothesis. The contrast tests Snedecor F for ANOVA two tail and two-sample Tstudent test suggested the effectiveness of the learning tool proposed.